2016
DOI: 10.1007/s10620-016-4107-4
|View full text |Cite
|
Sign up to set email alerts
|

How Do We Manage Gastric Intestinal Metaplasia? A Survey of Clinical Practice Trends for Gastrointestinal Endoscopists in the United States

Abstract: There is variability in the knowledge and practice patterns of US endoscopists related to surveillance of gastric intestinal metaplasia. In the absence of detailed US GI society guidelines, many endoscopists perform surveillance endoscopy on patients with GIM using variable biopsy techniques and surveillance intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
2
17
2
Order By: Relevance
“…Importantly, 97% of respondents felt that societal guidelines for management of premalignant gastric lesions would be beneficial to clinical practice[ 39 ]. These results were further supported by a study by Vance et al[ 40 ] that showed “variability in the knowledge and practice patterns of United States endoscopists related to surveillance of gastric intestinal metaplasia”.…”
Section: Discussionsupporting
confidence: 66%
“…Importantly, 97% of respondents felt that societal guidelines for management of premalignant gastric lesions would be beneficial to clinical practice[ 39 ]. These results were further supported by a study by Vance et al[ 40 ] that showed “variability in the knowledge and practice patterns of United States endoscopists related to surveillance of gastric intestinal metaplasia”.…”
Section: Discussionsupporting
confidence: 66%
“…Similarly, the biopsy protocol performed during endoscopies was heterogeneous (in number and site), and did not always follow the current recommendations that indicate that at least 2 antral and 2 corpus biopsies should be obtained. Other studies have also reported a low adherence to the guidelines [23], and one study performed in the United States showed that 75% of gastroenterologists were even not aware of the existence of guidelines for the surveillance and management of IM [24].…”
Section: Discussionmentioning
confidence: 99%
“…5 Surveys of US endoscopists have found wide variation in practice patterns in the management of GIM, even among physicians regularly caring for populations that could be at increased risk based on race/ethnicity and/or immigration status. 8 An evidencebased guideline supported by a comprehensive literature review for management of patients with GIM has not been previously published in the United States. Accordingly, we aimed to develop evidence-based guidelines to inform management of patients with GIM incidentally detected on gastric biopsies in routine clinical practice.…”
mentioning
confidence: 99%